EFEKTIVITAS PENGEMBALIAN ASET HASIL TINDAK PIDANA KORUPSI SEBAGAI UPAYA PEMBERANTASAN KORUPSI DI INDONESIA - Mohamad Djatmiko (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2025)
Corruption crimes in Indonesia have not been prevented and addressed to the maximum extent, thus harming the people, the nation, and the state of Indonesia. As a result of these corruption crimes, poverty, unemployment, low levels and quality of education, insufficient health standards, and deep economic disparities between a small wealthy group and the majority of the poor population have emerged. This situation can lead to social conflicts that harm community, national, and state life. One of the reasons for the failure to address corruption crimes is that the perpetrators and potential perpetrators of corruption feel that the legal sanctions they would receive if their corruption is uncovered are not too severe, and the perpetrators along with their families can still enjoy the spoils of corruption for generations. This is due to the still limited assets resulting from corruption crimes that can be returned to the state using the current legal system. Thus, the doctrine of crime does not pay, which means that perpetrators of crimes should not benefit from the proceeds of their crimes, cannot be implemented. Therefore, it is necessary to make a breakthrough by enacting the Draft Law on Asset Forfeiture of Crime Proceeds, which has adopted the results of the UN Convention Against Corruption (UNCAC) of 2003 into the legal system in Indonesia. Certainly, before this Law on Asset Forfeiture of Crime Proceeds is enacted, improvements are needed, both regarding the substantial legal provisions, the preparation of professional and high-integrity law enforcement officers, enhancing international cooperation in the recovery of corruption assets stored abroad, as well as creating a clean government and good governance.